ELLIPIS IN OCEAN’S ELEVEN MOVIE - Ester Br. Tarigan; Immanuel Prasetya Gintings (State University of Medan, 2015)
This study deals with ellipsis in Ocean’s Eleven movie. The objectives of this studyare to describe the types of ellipsis and the cause of ellipsis within the movie. themethod of research is library research by reading some books related to this study.The data of this research are divided into 2, the data for research problem no. 1 aretaken from conversation that have been chosen from some scenes and the data forresearch problem no. 2 are taken from transcript of characters of different profession(robbers and entrepreneurs). The technique of analyzing data is documentarytechnique, for research problem no. 1 the techniques are identifying the data,classifying the data and counting the occurrence of ellipsis and for research problemno.2 the techniques are identifying the data, counting the number of ellipsis by eachprofession and finding out the cause of ellipsis. The findings of research problemno.1 showed that the three types of ellipsis are used in the movie namely: (1).Nominal ellipsis (34.8%), (2). Verbal ellipsis (2.2%), (3). Clausal ellipsis (63,0%).The findings of research problem no.2 showed that the use of ellipsis by the robbersis about (64%) and the entrepreneur is about (36%). By this finding can be concludedthat ellipsis can be caused by one’s profession related to the purpose.